Gaharu (agarwood) distillate-incorporated roselle health drink - Hashim, Yumi Zuhanis Has-Yun; Jaswir, Irwandi; M. Gameil, Abeir Hussein; Idris, Iswadi; Mohammed Ab Halim, Mohammed Fitri; Mohd. Salleh, Hamzah; Jamal, Parveen; Amid, Azura; Abbas, Phirdaous (2013)
In this work, a nutraceutical product based on Gaharu distillate was developed. Gaharu (Agarwood) is a scented resin produced by trees of the Aquilaria species upon infection by fungus. While various components and parts of Gaharu tree have traditionally been reported to have medicinal values, it is the resin that is most sought after. Meanwhile, less have been focused on the distillates, a waste by-product of Gaharu oil distillation process. In this study, Gaharu distillate was found to have acidic pH of 3.60 and safe for consumption as it is devoid of steroids, has total suspended solid of less than 25 mg/L and an LC50 of 398000 ppm based on Brine Shrimp Lethality Assay. Gaharu distillate was also found to have antioxidant and antimicrobial properties as well as being selective towards killing cancer cells. To increase market acceptability, formulation of Gaharu distillate incorporated Roselle health drink was developed and optimized. By discovering, developing and commercializing new use of Gaharu distillates(coupled with scientific evidences on safety and potential health benefits), we can ensure the sustainability of Gaharu industry as well as provide new means of income-generating activities.